Identity Crisis and Social Adjustment in Nomadic and Shiraz Adolescents: A Causal-Comparative Study - Marselovna Galimardanova, Yulia (2021)
At present, the execution of help and guaranteeing the improvement of little and medium-sized organizations in the Russian Federation is quite possibly the main undertakings of the state. The essential errand of state charge guideline is to guarantee such a component for burdening the exercises of little and medium-sized organizations, in which, from one perspective, the ideal degree of taxation rate is guaranteed, and then again, there are steady and unsurprising assessment incomes to the spending framework. One of the instruments of duty guideline are uncommon expense systems that offer help and improvement of little and medium-sized organizations, work on the component of tax collection and assessment organization, and advance the taxation rate. In addition, it is prescribed to expand the strategy for the use of the patent tax assessment framework to citizens - legitimate substances, which will permit the patent tax collection framework to be applied to a more extensive scope of people and will build its fame.